(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Now a day, human health is dynamically disturbed by many factors in the modern society. Chronic inflammation is the foremost underlying cause in non-communicable diseases like Diabetes, cancer, arthritis, coronary artery disease etc. Ample studies advocate the idea of inflammatory process contribute to adverse health outcomes in the modern society. The physiological link between obesity, cardiovascular disease, T2DM, and cancer are signaling through accumulation of overwhelmed Agni of the subtle body in turn enhances oxidative stress and induces inflammation in the physical body. Regular practice of yoga and meditation boost up the ability to minimize inflammatory responses to stressful encounters and also limits stress related changes to stay with substantial health benefits. Yoga as a lifestyle along with oil bath, yoga nidra, pranayamam, meditation are unique gifts to human beings for maintaining healthy life by natural way.